Experiences with rotavirus vaccines: can we improve rotavirus vaccine impact in developing countries?. Issue 6 (3rd June 2019) - Steele, A.D.; Victor, J.C.; Carey, M.E.; Tate, J.E.; Atherly, D.E.; Pecenka, C.; Diaz, Z.; Parashar, U.D.; Kirkwood, C.D.
ABSTRACT: Rotavirus vaccines have been introduced into over 95 countries globally and demonstrate substantial impact in reducing diarrheal mortality and diarrheal hospitalizations in young children. The vaccines are also considered by WHO as "very cost effective" interventions for young children, particularly in countries with high diarrheal disease burden. Yet the full potential impact of rotavirus immunization is yet to be realized. Large countries with big birth cohorts and where disease burden is high in Africa and Asia have not yet implemented rotavirus vaccines at all or at scale. Significant advances have been made demonstrating the impact of the vaccines in low- and lower-middle income countries, yet the modest effectiveness of the vaccines in these settings is challenging. Current research highlights these challenges and considers alternative strategies to overcome them, including alternative immunization schedules and host factors that may inform us of new opportunities.